Linking brain electrical signals elicited by current outcomes with future risk decision-making - Zhang, Dandan; Gu, Ruolei; Broster, Lucas S.; Jiang, Yang; Luo, Wenbo; Zhang, Jian; Luo, Yuejia (Frontiers in Behavioral Neuroscience, 2014)
The experience of current outcomes influences future decisions in various ways. The neural mechanism of this phenomenon may help to clarify the determinants of decision-making. In this study, thirty-nine young adults finished a risky gambling task by choosing between a high- and a low-risk option in each trial during electroencephalographic data collection. We found that risk-taking strategies significantly modulated mean amplitudes of the event-related potential (ERP) component P3, particularly at the central scalp. The event-related spectral perturbation and the inter-trial coherence measurements of the independent component analysis (ICA) data indicated that the “stay” vs. “switch” electrophysiological difference associated with subsequent decision-making was mainly due to fronto-central theta and left/right mu independent components. Event-related cross-coherence results suggested that the neural information of action monitoring and updating emerged in the fronto-central cortex and propagated to sensorimotor area for further behavior adjustment. Based on these findings of ERP and event-related oscillation (ERO) measures, we proposed a neural model of the influence of current outcomes on future decisions.